Risk pump in Gerbillus pyramidum: quality of poor habitats increases with more conspecifics. Issue 2 (4th March 2019) - Menezes, Jorge F.S.; Kotler, Burt P.; Dixon, Austin K.
Abstract : Reducing predation risk is fundamental to many animals. Among those, social animals are studied for one type of anti-predator defense. They aggregate in certain habitats to dilute risk, share vigilance, defend each other, and reduce their chances of being attacked. However, this tendency is not necessarily unique: solitary animals may also benefit from the presence of conspecifics. Thus, we hypothesize that even solitary animals should aggregate whenever there is safety in numbers. Additionally, this tendency to aggregate should create a "risk pump", a positive feedback in aggregation because more individuals bring more safety, which brings more individuals. We also analyzed if they will aggregate in resource-rich or resource-poor environment. Aggregation in a richer and thus crowded environment implies risk pump is a stronger mechanism than competition. Aggregation in a resource-poor environment indicates the presence of risk pump, but one weaker than competition. To test the existence and direction of a "risk pump" in non-social animals, we compared quality between patches at different distances and population densities in three experiments. We used the most abundant gerbils of the Negev Desert: Gerbillus andersoni and G. pyramidum . Results supported the hypothesis of aggregation in the resource-poor patch for both species.